Gambaran Tingkat Penyesuaian Diri Siswa Suku Jawa di Jabodebek - Eustalia Wigunawati; Flovloni Mirzanadya Marbeliz (Fakultas Psikologi Universitas Sanata Dharma, 2022)
This study aims to describe the adjustment of Javanese students living in the Greater Jakarta area. Respondents were students of class X and XI Javanese high school in Jakarta, Bogor, Depok and Bekasi totaling 135 students. This study uses a quantitative descriptive method. The sampling technique used in this research is purposive sampling. The research data was obtained using the Adjustment Scale with a reliability coefficient of Cronbach alpha of 0.751. The data analysis technique used quantitative descriptive analysis based on the percentage of gender, grade level, and aspects of adjustment. The results of the study based on hypothetical data showed that Javanese students had moderate and high levels of adjustment. There is no adjustment of students who are in the low category. This shows that if generalized, Javanese students have good self-adjustment. Based on empirical data, more Javanese students have self-adjustment in the low category than in the high category, which is 26.67%. Based on gender, male students' adjustment was more in the high category than in the low category; while the adjustment of female students was in the low category compared to the high category. Based on class groups, it shows that there are still many class X and class XI who have self-adjustment in the low category. Based on the aspect of adjustment, it shows that from all aspects of adjustment, more students are in the low category than high. Aspects of individual ability in overcoming anxiety and stress are dominated in the low category, namely 51.85%. Keywords: adjustment, students, Javanese